2021
DOI: 10.1021/acs.cgd.0c01605
|View full text |Cite
|
Sign up to set email alerts
|

Speciation of Substituted Benzoic Acids in Solution: Evaluation of Spectroscopic and Computational Methods for the Identification of Associates and Their Role in Crystallization

Abstract: Self-association of four benzoic acid derivatives 2chloro-4-nitrobenzoic acid, 2-methyl-4-nitrobenzoic acid, 3hydroxybenzoic acid, and 2,6-dimethoxybenzoic acid in solution was investigated using spectroscopic measurements (Fourier transform infrared and 1 H and 13 C NMR spectroscopy) and molecular simulation methods. Based on the formation of hydrogen bonds, solvents can be divided into two groups: apolar solvents or solvents with a low hydrogen bond acceptor propensity, in which the benzoic acid derivatives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 82 publications
(147 reference statements)
0
5
0
Order By: Relevance
“…Second, we selected this compound to try to find an approach for additive crystallization that would allow a reliable preparation procedure for the disappearing polymorphs. Our previous study [47] has already confirmed that polymorphs II and III can be obtained by varying the crystallization conditions. In this study, we additionally characterized forms I and III, performed screening of additives allowing control of the polymorphic outcome in the crystallization, explored the most promising additives for the crystallization control, and explored the effect of additives on phase transitions.…”
Section: Introductionmentioning
confidence: 52%
“…Second, we selected this compound to try to find an approach for additive crystallization that would allow a reliable preparation procedure for the disappearing polymorphs. Our previous study [47] has already confirmed that polymorphs II and III can be obtained by varying the crystallization conditions. In this study, we additionally characterized forms I and III, performed screening of additives allowing control of the polymorphic outcome in the crystallization, explored the most promising additives for the crystallization control, and explored the effect of additives on phase transitions.…”
Section: Introductionmentioning
confidence: 52%
“…It was hypothesized that the structural motifs of API dimers in solution encode the polymorphic outcomes of crystal nucleation. As such, MD simulations of organic molecules in solutions have focused on the association of monomer building blocks to support experimental studies 127–131 . In simple 2D models of flexible chiral molecules, Carpenter and Grünwald 132 recently demonstrated how bulk crystal structures are related to the organization of building blocks prior to nucleation and the importance of kinetics in predicting polymorphism.…”
Section: Modeling Approaches To Simulate Nucleation From Solutionmentioning
confidence: 99%
“…As such, MD simulations of organic molecules in solutions have focused on the association of monomer building blocks to support experimental studies. [131,132,133,134,135] In simple 2D models of flexible chiral molecules, Carpenter and Grünwald [136] recently demonstrated how bulk crystal structures are related to the organisation of building blocks prior to nucleation and the importance of kinetics in predicting polymorphism.…”
Section: Prenucleation Speciesmentioning
confidence: 99%